Expression of transgenes enriched in rare codons is enhanced by the MAPK pathway - Jackson Peterson (Nature Portfolio, 2020)
Abstract The ability to translate three nucleotide sequences, or codons, into amino acids to form proteins is conserved across all organisms. All but two amino acids have multiple codons, and the frequency that such synonymous codons occur in genomes ranges from rare to common. Transcripts enriched in rare codons are typically associated with poor translation, but in certain settings can be robustly expressed, suggestive of codon-dependent regulation. Given this, we screened a gain-of-function library for human genes that increase the expression of a GFPrare reporter encoded by rare codons. This screen identified multiple components of the mitogen activated protein kinase (MAPK) pathway enhancing GFPrare expression. This effect was reversed with inhibitors of this pathway and confirmed to be both codon-dependent and occur with ectopic transcripts naturally coded with rare codons. Finally, this effect was associated, at least in part, with enhanced translation. We thus identify a potential regulatory module that takes advantage of the redundancy in the genetic code to modulate protein expression.